Serological and molecular prevalence of west nile virus infection in wild birds, macaques and bats in selected areas in Peninsular Malaysia - Mohd Yuseri, Nur Ain Najwa (2019)
West Nile virus (WNV) is the aetiological agent for mosquito-borne zoonotic virus which originated from a genus of Flavivirus and belongs to the family of Flaviviridae. WNV transmission cycles involve birds as a reservoir host, mosquitoes as the vector while susceptible animals mainly mammals are the incidental hosts. In Malaysia, seropositivity and nucleic acid detection of WNV have been demonstrated in captive birds, Orang Asli and horses. Previous studies have very limited information on the status of WNV in wildlife. On the other hand, other wildlife such as macaques and bats are renowned as a reservoir for deadly zoonotic viruses such as Ebola, Marburg, Severe Acute Respiratory Syndrome (SARS) Coronavirus and Henipavirus, and they also have been demonstrated to shed WNV in other countries. By considering all these facts and WNV has become a global threat to the public health, this study aimed to determine the seroprevalence (antibody) and molecular prevalence (nucleic acid) status of WNV in wildlife particularly wild birds, macaques and bats from selected areas in Peninsular Malaysia. In addition to that, risk factors associated with WNV seropositivity and infection were identified. The serum was collected from 236 (n=236) wild birds and macaques in selective states of Perak, Pahang, Selangor and Johor and followed by screened for WNV antibodies by using commercial competitive ELISA (c-ELISA) kit (ID Screen® West Nile Competition Multi-species ELISA, ID VET, Montpellier, France). Due to the cross-reaction with another genus of Flavivirus, the samples tested seropositive to WNV were further analysed by using Japanese encephalitis virus (JEV) double-antibody sandwich ELISA (DAS-ELISA) kit (Sunred, China). In addition, a total of 240 oropharyngeal and rectal swabs from wild birds, macaques and bats were collected in selective states of Perlis, Perak, Pahang, Selangor and Johor. The swabs were subjected to one-step RT-PCR assay to detect WNV nucleic acids by targeting the conserved region of WNV between capsid and pre-membrane regions. The positive band from RT-PCR assay were subjected to DNA sequencing and phylogenetic tree analyses. The risk factors associated with WNV exposure from ELISA result and infection from RT-PCR result in wildlife were analysed by using Chi-square (X2), Fisher’s exact test, multiple logistic regression and student t-test. The prevalence was calculated as a percentage for the positive samples. The seroprevalence of WNV in this study are 18.71% (29/155) at 95% CI (0.131 to 0.260) in wild birds and 29.63% (24/81) at 95% CI (0.203 to 0.410) in macaques. In wild birds, significant risk factors associated with WNV seroprevalence are a category of wild bird, family, species, age, locality, presence of paddy field and migratory period. In macaques, all risk factors include age and sex were not significantly associated with WNV seroprevalence. Molecular analysis by using RT-PCR revealed that 15.2% (16/105) at 95% CI (0.092 to 0.239) of wild birds, 8.3% (6/72) at 95% CI (0.034 to 0.179) of bats and none of the macaque samples were positive. Sequencing analysis by using DNA Sanger sequencing method showed that the positive samples in this study resembled 98-99% similarity and closely related to the strain from South Africa in lineage 2 of WNV. Overall, this is the first study to investigate WNV status in wildlife in Peninsular Malaysia as well as the risk factors associated with WNV exposure and infection. Although there is no WNV outbreak in Malaysia and no clinical reports of WNV infections have been made yet, precaution and preventive measures should be taken as WNV could possibly become pathogenic to animals and humans.